A randomised double-blind pilot trial comparing a mean arterial pressure target of 65 mm Hg versus 72 mm Hg after out-of-hospital cardiac arrest. Issue 4 (1st November 2020) - Grand, Johannes; Meyer, Anna SP; Kjaergaard, Jesper; Wiberg, Sebastian; Thomsen, Jakob H; Frydland, Martin; Ostrowski, Sisse R; Johansson, Pär I; Hassager, Christian
Abstract : Background: After resuscitation from out-of-hospital cardiac arrest, mean arterial pressure below 65 mm Hg is avoided with vasopressors. A higher blood-pressure target could potentially improve outcome. The aim of this pilot trial was to investigate the effect of a higher mean arterial pressure target on biomarkers of organ injury. Methods: This was a single-centre, double-blind trial of 50 consecutive, comatose out-of-hospital cardiac arrest patients randomly assigned in a 1:1 ratio to a mean arterial pressure target of 65 mm Hg (MAP65) or 72 mm Hg (MAP72). Modified blood pressure modules with a –10% offset were used, enabling a double-blind study design. End-points were biomarkers of organ injury including markers of endothelial integrity (soluble trombomodulin) brain damage (neuron-specific enolase) and renal function (estimated glomerular filtration rate). Results: Mean arterial pressure was significantly higher in MAP72 with a mean difference of 5 mm Hg ( p group =0.03). After 48 h, soluble trombomodulin (median (interquartile range)) was 8.2 (6.7–12.9) ng/ml and 8.3 (6.0–10.8) ng/ml ( p =0.29), neuron-specific enolase was 20 (13–31 μg/l) and 18 (13–44 μg/l) p =0.79) and estimated glomerular filtration rate (mean (±standard deviation)) was 61±19 ml/min/1.73m2 and 48±22 ml/min/1.73 m2 ( p =0.08) for the MAP72 and MAP65 groups, respectively. Renal replacement therapy was needed in eight patients (31%) in MAP65 and three patients (13%) in MAP72 ( p =0.14). Conclusions: Double-blind allocation to different mean arterial pressure targets is feasible in comatose out-of-hospital cardiac arrest patients. A mean arterial pressure target of 72 mm Hg compared to 65 mm Hg did not result in improved biomarkers of organ injury. We observed a trend towards preserved renal function in the MAP72 group.